Intravenous immunoglobulin: prospects in patients with autoimmune rheumatic diseases - Elena Aleksandrovna Aseeva; S K Solov’ev (Современная ревматология)
The published data on efficiency of intravenous immunoglobulin (IVIG) in patients with autoimmune rheumatic diseases (RD) are analyzed. IVIG is the drug of choice in patients with Kawasaki disease, idiopathic thrombocytopenic purpura, dermatomyositis, etc. It is reasonable to use IVIG in RD patients with immune deficiency, infectious complications, ineffectiveness of glucocorticoid and cytostatic treatment in patients with developing autoimmune cytopenia, central nervous system dysfunction, and vasculitis. In patients with antiphospholipid syndrome, IVIG can be effective in case of the risk of miscarriage and ineffective anticoagulant therapy.